2021
DOI: 10.1101/2021.12.08.471623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The UV RESISTANCE LOCUS 8-Mediated UV-B Response Is Required Alongside CRYPTOCHROME1 For Plant Survival Under Sunlight In The Field

Abstract: As sessile organisms, plants are subjected to fluctuating sunlight including potentially detrimental ultraviolet-B radiation (UV-B). In Arabidopsis thaliana, experiments under controlled conditions have shown that UV RESISTANCE LOCUS 8 (UVR8) controls photomorphogenic responses for acclimation and tolerance to UV-B; however, its long-term impacts on plant performance remain poorly understood in naturally fluctuating environments. Here we quantified the survival and reproduction of different Arabidopsis mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Field observations of A. thaliana and its relatives will enable the study of plant responses in the field, taking the advantage of a large number of studies in regulated chambers as well as mutant collections. For example, destructive sampling of A. thaliana showed that anthocyanin content was reduced in the double mutants of UVR8 and CRY1 photoreceptor genes in the field 62 , which can be extended to time-course studies. By connecting to solar power, PlantServation can be deployed at remote natural sites to observe diverse species.…”
Section: Discussionmentioning
confidence: 99%
“…Field observations of A. thaliana and its relatives will enable the study of plant responses in the field, taking the advantage of a large number of studies in regulated chambers as well as mutant collections. For example, destructive sampling of A. thaliana showed that anthocyanin content was reduced in the double mutants of UVR8 and CRY1 photoreceptor genes in the field 62 , which can be extended to time-course studies. By connecting to solar power, PlantServation can be deployed at remote natural sites to observe diverse species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that controlled laboratory conditions are unlikely to reflect outdoor environments where interspecific interactions typically occur [19,20]. This fact emphasizes the importance of in natura studies of functional genes [21][22][23][24][25]. To achieve this goal, it is important to conduct GWAS under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana is a model plant species distributed and naturalized around the world. While A. thaliana usually blooms in spring after over-wintering, some cohorts have overlapping life cycles from spring to autumn [25][26][27]. When A. thaliana plants emerge from late spring to early summer, they are threatened by various herbivores [4,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that controlled laboratory conditions are unlikely to reflect outdoor environments where interspecific interactions typically occur [17,18]. This fact emphasizes the importance of in natura study of functional genes [19][20][21][22][23]. To achieve this goal, it is important to conduct GWAS under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana is a model plant species distributed and naturalized around the world. While A. thaliana usually blooms in spring after over-wintering, some cohorts have overlapping life cycles from spring to autumn [2325]. When A. thaliana plants emerge from late spring to early summer, they are threatened by various herbivores [4,26].…”
Section: Introductionmentioning
confidence: 99%